(untitled) (Rivista di Studi e Ricerche sulla criminalità organizzata, 2023)
By retracing the lesson held by the Pasquale Angelosanto division - commander of the Carabinieri Special Operations Group (ROS) - at the University of Milan, the article addresses the key points on which the intelligence activity is based, highlighting its multipurpose connotation, i.e. to be understood both as a law enforcement activity and as a defensive activity.